P038 NETWORK META-ANALYSIS: COMPARATIVE EFFICACY OF BIOLOGICS IN THE TREATMENT OF BIOLOGIC-NAïVE JAPANESE PATIENTS WITH MODERATELY TO SEVERELY ACTIVE ULCERATIVE COLITIS. (7th February 2019) - Hibi, Toshihumi; Kamae, Isao; Pinton, Philippe; Ursos, Lyann; Iwakiri, Ryuichi; Hather, Greg; Patel, Haridarshan
Abstract: Background: There are several biologic therapies approved in Japan for moderate-to-severe ulcerative colitis (UC) but there are no head-to-head randomized controlled trials (RCTs) or network meta-analysis (NMA) for comparing their efficacy. We aimed to compare the efficacy of biologics approved in Japan (adalimumab, infliximab, golimumab, and vedolizumab) for treating moderate-to-severe UC biologic-naïve patients. Methods: A targeted review of the literature was conducted to identity published RCTs for these biologics in UC. Outcomes of interest included clinical response, clinical remission, and mucosal healing. For each outcome, the treatment effect (reported as a probability with a 95% confidence interval) relative to placebo was estimated using an NMA for induction and maintenance. Only approved dosing of each drug was considered. Results: 4 RCTs were included. Probabilities of clinical response, clinical remission, and mucosal healing during both induction and maintenance are reported in Table 1. During induction, the probability of clinical remission was highest with vedolizumab (23.6%) and clinical response and mucosal healing were highest with infliximab (55.1% and 48.4% respectively). In maintenance, the probability of clinical response, clinical remission and mucosal healing were highest with golimumab. Furthermore, the probability of clinical response (53%) and mucosal healing (45.6%) were higher with vedolizumab compared to adalimumab (38.8% and 37.5% respectively). Clinical remission probability was higher (38.3% vs 25.2%) with adalimumab compared to vedolizumab. The probabilities for each outcome with each therapy were not statistically different. Conclusion: There is limited data comparing biologics among Japanese population with UC. Our initial analysis in biologic-naïve patients with UC showed that vedolizumab and infliximab had highest probabilities for induction of clinical response, remission and mucosal healing in Japanese patients with UC. Maintenance probability rates showed that golimumab had the highest likelihood of maintaining these outcomes. Vedolizumab had higher likelihood of clinical response and mucosal healing vs. adalimumab in this cohort while adalimumab had a higher likelihood of maintaining clinical remission. A limitation of this analysis is that study differences were not accounted for and further analysis should control for such differences. The placebo rates for adalimumab and golimumab were lower than vedolizumab which may have impacted the results of this analysis. To our knowledge this is the first NMA looking at Japanese biologic-naïve UC patients demonstrating relative efficacy for approved biologics in Japan. Results of this analysis are not generalizable to other populations and need confirmation in real-world settings with larger sample sizes.